(untitled) (Research, Society and Development, 2022)
Introduction: Brain death (BD) is the irreversible cessation of the functions of intracranial neurological structures, fulfilling prerequisites such as coma with known and irreversible cause; absence of hypothermia, hypotension or severe metabolic disorder and exclusion of intoxication or depressive effect of the central nervous system. Methodology: Approved by the Research Ethics Committee (CEP/ UFU), used data from patients of the Adult Intensive Care Unit of the Hospital de Clínicas of the Federal University of Uberlândia (UTIA/ HC-UFU) in a state of coma for which the Brain Death Diagnostic Protocol was opened with graphic examination, proceeding descriptive and statistical analysis. Results: present male profile, aged >41 years, born in other municipalities, with complete elementary school. Presenting 52.68% of the cases of etiology by TBI, from traffic accident 23.65%, 7.53%, gunshot wound 6.45%, beating 5.38% and other 21.51%; most did not have comorbidities (50.53%)and alcoholism also appear in greater percentage and age over 44 years. Discussion: The main causes of ED were cranioencephalic trauma (TBI), stroke (CVA) and ischemic hypoxia (HI) after cardiac arrest. All open protocols for diagnosis of BD evolved to death, and no case of opening of the protocol with improvement of the individual was found. Conclusion: the predominant profile was greater than 40 years, residents outside Uberlândia and of average schooling consisting of complete elementary school, victims of stroke or trauma, in use of sedatives, with significant increase of CO2 pressure and reduction of O2 pressure (p <0.001) between the beginning of hospitalization and the outcome of the condition. The main findings of the patients admitted were the presence of comorbidities, the use of sedatives and significant worsening in laboratory tests.